"VACUOLE" SIGN ADJACENT TO RETINAL PIGMENT EPITHELIAL DEFECTS ON SPECTRAL DOMAIN OPTICAL COHERENCE TOMOGRAPHY IN CENTRAL SEROUS CHORIORETINOPATHY ASSOCIATED WITH SUBRETINAL FIBRIN. Issue 2 (February 2017) - Rajesh, Bindu; Kaur, Amardeep; Giridhar, Anantharaman; Gopalakrishnan, Mahesh
Abstract : Purpose: To report spectral domain optical coherence tomography features in central serous chorioretinopathy associated with subretinal fibrin. Method: Retrospective observational case series of patients with central serous chorioretinopathy with subretinal fibrin imaged with spectral domain optical coherence tomography. Result: Twenty-three eyes of 23 patients (19 males and 4 females), with mean age of 39.09 ± 5.8 years were included in the study. Subretinal fibrin clinically ranged from localized well-defined areas to extensive ill-defined areas. Along with the presence of subretinal hyperreflectivity (n = 23, 100%), corresponding to fibrin, spectral domain optical coherence tomography also revealed the presence of the retinal pigment epithelial (RPE) defects (n = 23, 100%) in all eyes with an adjacent well-defined hyporeflective vacuole. In 19 eyes wherein fundus fluorescein was performed, the RPE defects and vacuoles corresponded to the site of RPE leak. Serous pigment epithelial detachments (n = 18, 78.2%), multiple RPE defects in the same eye (n = 5), and multiple RPE defects in same pigment epithelial detachment (n = 1) were few other interesting features observed. Conclusion: The presence of a hyporeflective vacuole amid the hyperreflective fibrin adjacent to RPE defects probably indicates the site of constant fluid egress and is an important sign of disease activity especially in cases where fundus fluorescein angiography is not possible. Abstract : Retrospective analysis of SD-OCT images of central serous chorioretinopathy associated with subretinal fibrin revealed hyporeflective area (vacuoles) in all cases adjacent to retinal pigment epithelial defects, which could indicate site of constant fluid egress and disease activity.